The Issue of Overestimating the Final Price in Online Auctions In The Context of User Experience – Based on Selected EEU Markets - Lukasz ZAKONNIK; Grzegorz PODGORSKI; Piotr CZERWONKA (Communications of International Proceedings, 2022)
In the article, the authors ask whether and to what extent does the experience of the buyer play a role in overestimating the final price in online auctions (winner's curse). The article, as part of the expert study, defines how the buyer's experience is understood and specifies 6 assumptions. The verification of the assumptions, in most cases, indicated that the victims of the winner's curse are people with less experience, only in one case the opposite situation occurred –  it was dictated by the use of programs that automatically, on behalf of the user, submit an offer at the last possible moment of the auction (the so-called sniper). The article suggests the possibility of managing the risk of an unfavorable transaction.
Keywords: e-commerce; transaction cost; online auction; user behavior; online auction risk management